Type III Interferons in Hepatitis C Virus Infection - Boisvert, Maude; Shoukry, Naglaa H. (Frontiers in Immunology, 2016)
The IFN-lambda family of type III cytokines includes the closely related IL28A (IFN-lambda 2), IL28B (IFN-lambda 3) and IL-29 (IFN-lambda 1). They signal through the Jak-STAT pathway and promote an anti-viral state by the induction of expression of several interferon stimulated genes (ISGs). Contrary to type I IFNs, the effect of IFN-lambda cytokines is largely limited to epithelial cells due to the restricted pattern of expression of their specific receptor. Several genome wide association studies (GWAS) have established a strong correlation between polymorphism in the region of IL28B gene (encoding for IFN-lambda 3) and both spontaneous and therapeutic IFN-mediated clearance of hepatitis C virus (HCV) infection but the mechanism(s) underlying this enhanced viral clearance are not fully understood. IFN-lambda 3 directly inhibits HCV replication and in vitro studies suggest that polymorphism in the IFN-lambda 3 and its recently identified overlapping IFN-lambda 4 govern the pattern of ISGs induced upon HCV infection of hepatocytes. IFN-λ can also be produced by dendritic cells and apart from its antiviral action on hepatocytes, it can regulate the inflammatory response of monocytes/macrophages thus acting at the interface between innate and adaptive immunity. Here, we review the current state of knowledge about the role of IFN-lambda cytokines in mediating and regulating the immune response during acute and chronic HCV infection.